A novel mechanism and model of hydrogen isotope exchange in vacancy considering nuclear quantum effects - Qihang Liu; Fei Sun; Jipeng Zhu; Hai-Shan Zhou; Hongxiang Zong; Zhangcan Yang; Hong-Bo Zhou; Yasuhisa Oya; Yucheng Wu (Nuclear Fusion, 2024)
Tritium (T) retention in plasma-facing materials (PFMs) raises significant radiological safety concerns and adversely affects the self-sustained burning of T in fusion reactors. Therefore, the removal of retained T from PFMs has become an urgent task. Hydrogen isotope (HI) exchange has proven to be an effective method for T removal. However, the microscopic mechanisms, particularly the role of isotope effects, remain insufficiently understood. For the first time, this work employs path integral molecular dynamics to account for the nuclear quantum effects of HIs and explore the microscopic mechanisms of HI exchange in tungsten (W) vacancies. Atomic-scale simulations reveal that the fundamental principle of HI exchange is the reduction in binding energy between HIs and vacancies as the defect filling level increases, involving two key processes: de-trapping and trapping. These processes are influenced by isotope effects, with pronounced differences observed at low temperatures. Notably, T exhibits a higher probability of de-trapping from vacancies compared to hydrogen (H), while vacancies demonstrate a stronger affinity for trapping H. In contrast, the isotope effect is less pronounced between deuterium (D) and H, leading to different exchange efficiencies between H and T, as well as between D and T. Based on these isotope effects, we proposed a detailed microscopic mechanism for HI exchange in vacancies and developed a T evolution model that accounts for variations in HI concentrations. This work advances our understanding of HI exchange for T removal applications and offers a more accurate assessment of T retention in future D–T environments.